ANALYSIS OF LOCAL WISDOM-BASED COLLABORATION SKILL INSTRUMENT (LWCSI) IN CIVICS FOR HIGHER EDUCATION - Tirza, Juliana; Parwati, Ni Nyoman; Dantes, Gede Rasben; Suartama, I Kadek (IJIET (International Journal of Indonesian Education and Teaching), 2024)
The ability to collaborate is highly important in the world of work and social life. This skill is related to the individual's ability to cooperate with others in achieving a goal. Several previous studies related to the development of collaboration ability instruments using visible dimensions as their pivot, such as aspects of performance outcomes and levels of interaction. However, some previous studies suggest that a person's ability to collaborate comes from within as well. Therefore, an instrument is needed to measure students' collaborative abilities in depth and adapt to the diverse Indonesian context, which is diverse in so many aspects. The researchers developed an instrument called the Local Wisdom-Based Collaboration Skills Instrument (LWCSI), which is an instrument that measures students' collaboration abilities but is adapted to the context of Indonesia which is Godly and diverse in culture. The population in this study consisted of 166 students who took civics education classes in the short semester of 2022/2023. To determine the validity, the df value used is (166-2) = 164 with an α value of 0.05. The R-table value obtained is 0.1281. From the table the R-count is greater than the R-table, so it can be concluded that all items are valid. The number shows 0.06 so it can be concluded that the LWCSI instrument is reliable and can be utilized to measure student collaboration skills based on local wisdom. Therefore, it can be concluded that this instrument is able to measure the collaboration skills of students with a variety of beliefs and cultures, especially in Indonesia that have a large and diverse population.